(Invited) Material Considerations for the Development of III-Nitride Power Devices. (17th August 2017) - Sarkar, Biplab; Reddy, Pramod; Kaess, Felix; Haidet, Brian; Tweedie, James; Mita, Seiji; Kirste, Ronny; Kohn, Erhard; Collazo, Ramon; Sitar, Zlatko
Abstract : With advancement in growth of native III-nitride substrates, remarkable progress has been made to extend the functionality of GaN based power electronic devices. The low dislocation epitaxial films grown on native substrates outperforms the films grown on foreign substrates. However, several material considerations has to be incorporated in order to exploit the full potential of GaN and Alx Ga1-x N (0<x≤1) based power devices. This paper presents a review report on the development of III-nitride power devices grown on foreign and native (GaN and AlN) substrates. Discussion on state-of-the art epitaxial material quality, contact formation and surface treatments films are presented.